2021
DOI: 10.1007/s11629-021-7080-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of 137Cs and 210Pbex fallout radionuclides for spatial soil erosion and redistribution assessment on steeply sloping agricultural highlands

Abstract: which was either 166 or 398 Mg ha -1 yr -1 , depending on the soil erodibility factor (soil series factor and calculated factor from soil sample analysis) used in the model. We conclude that the FRN method using 137 Cs and 210 Pbex radionuclides can be used to assess soil erosion and redistribution in steeply sloping agricultural highlands. Verification of soil-erosion values using the FRN method and soil-erosion models has been controversial, but it merits further study at many locations with different soils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…As mentioned above, the results of this study show that the FRN concentration was related to SOM content (Table 1, Figure 3), similar to previous studies' findings [35,41]. These indicate that FRN concentrations may be largely dependent on SOM content.…”
Section: Differentiating the Potential Ss Sources By Binding Frns And...supporting
confidence: 91%
See 1 more Smart Citation
“…As mentioned above, the results of this study show that the FRN concentration was related to SOM content (Table 1, Figure 3), similar to previous studies' findings [35,41]. These indicate that FRN concentrations may be largely dependent on SOM content.…”
Section: Differentiating the Potential Ss Sources By Binding Frns And...supporting
confidence: 91%
“…FRNs can allocate the amount of SS contributed by each source via physical or biogeochemical properties [38,39]. Several researchers have explained that this method can determine soil and sediment redistribution dynamics within agricultural [40,41] and forested [31,36,42] catchments. Moreover, FRNs have been used to complement conventional methods for assessing SS movement and tracing SS sources within catchments [31,32,35].…”
Section: Introductionmentioning
confidence: 99%
“…Other previous studies have also demonstrated that diffuse run-off accounts for 75% of soil degradation. This is indeed an erosive process that occurs silently, but its longterm impact is very significant (Navas et al, 2011;Azaiez, 2016;Xu et al, 2019;Azaiez and Hamza, 2021;Yoon et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…First, existing relevant studies in the area were widely collected. Second, wind and water erosion rates of soils in agro-pastoral areas were assessed through field soil survey sampling combined with the use of well-established tracer methods [28][29][30][31][32][33][34] . This integrated approach enables the assessment of soil wind and water erosion rates in agropastoral areas and helps to determine their relative roles in this intertwined area.…”
mentioning
confidence: 99%